Acute Pseudomembranous Candidiasis in Patients with Hypertension - Siti Rusdiana Puspa Dewi; Lisa Triwardhani (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2020)
Introduction. Oral candidiasis is an opportunistic infection that is often found in the oral cavity caused by the growth of candida fungi. The calcium channel blocker antihypertensive drug, amlodipine, has a side effect that can reduce the amount of salivary flow, the reduced amount of saliva will cause anti-candida components in saliva such as lysozyme, histatin, lactoferrin, and calprotectin are also reduced, so that candida can easily develop in the oral cavity. This research was aimed to determine the management of cases of acute pseudomembranous candidiasis in hypertensive patients.Case presentation. A woman 16 years old came to the Mohammad Hoesin Hospital in Palembang with a complaint of a yellowish white spot on the upper surface of her tongue which she noticed since 2 weeks ago. The yellowish white patches feel sore when the patient brushes her tongue with a toothbrush. The patient wasuncomfortable with the state of her tongue so she wants her tongue to be treated. The patient had a history of hypertension since 1 year ago. The patient was given the drug nystatin drop. In the first control, 1 week after administration of the drug, white lesions on the tongue began to decrease and appear thinner compared to the previous visit. In the next control, the patient's tongue was clean so that the use of nystatin was stopped. The supporting investigation is a microbiological examination with a type of fungal culture against a tongue swab. The results of the examination indicated that the microscopic results of the yeast cell (+) KOH and the results of the germ culture in the form of Candida sp. The patient was diagnosed with acute pseudomembranous candidiasis and was treated with topical antifungals and was referred to an internal medicine specialist for hypertension control.Conclusion: Management of oral candidiasis is very important to know, and must be followed by controlling hypertension in the patient so that a good oral prognosis is obtained.